Evaluation of the association between haemoglobin levels and preterm birth at Khartoum, Sudan: A hospital-based study - Elmugabil, Abdelmageed; Alhabrdi, Nadiah M.; Rayis, Duria A.; Al-Wutayd, Osama; Adam, Ishag (Frontiers in Nutrition, 2022)
Objective: The objective of this study was to determine the association between haemoglobin level and PB. Methods: A cross-sectional study was conducted in Khartoum, Sudan. Questionnaires on demographics and medical and obstetric factors were completed. A logistic regression analysis was performed. Results: Of the 1716 pregnant women, approximately two-thirds (65.7%) had anaemia (haemoglobin <11 g/dl), and six (0.3%) had severe anaemia (haemoglobin <8g/dl). Of the 1716 women, 283 (16.5%) had a PB. In multivariable logistic regression, parity (AOR=1.15, 95% CI=1.09‒1.21, P<0.001) was positively associated with PB. Compared to those with haemoglobin levels of 10.0‒10.9 g/dl, pregnant women with haemoglobin levels of 8.0‒8.9 (AOR=0.41, 95% CI=0.22‒0.77), 9.0‒9.9 (AOR=0.59, 95% CI=0.38‒0.91) and 11.0‒11.9 g/dl (AOR=0.53, 95% CI=0.36‒0.77) were at lower risk of PB. Women with haemoglobin levels of 12–13 g/dl were at a higher risk of PB (AOR=1.62, 95% CI=1.06‒2.45). There was no significant association between women with haemoglobin levels <8.0 g/dl and >13.0 g/dl and PB. Conclusion: This study showed different levels of association between haemoglobin levels and PB.